Aspects of Small Claims Procedure in Colombia: A View from the Academy - Tapias Tapias, Amalia; Munóz Sanchéz, Rafael Evelio; Latorre Merchán, Rafael Ricardo (DIXI, 2016)
Introduction: Ths article is the result of research carried out by the research incubator of Procedural Law of the Bucaramanga Campus of the Universidad Cooperativa de Colombia (ucc). Methodology: Analysis of certain aspects of the new small claims procedure for declaratory judgment, which the General Procedure Code (cgp by its Spanish initials) successfully introduced into the legal system. Thse aspects are related to type, good faith of the creditor, exhaustion of procedural requirements, and propriety of interim measures. The analysis was performed pursuant to Articles 419 to 421 and 590 of the cgp, Law 640 of 2001, Decision C-726 of 2014 of the Constitutional Court of Colombia, and Calamandrei’s theory on small claims procedure. Results: Th legislature has shown the same procedural treatment to both pure and documentary small claims procedure, contrary to Calamandrei’s theory; the admission of pure small claims procedure implies that the judge supports the requirement of good faith payment to the creditor. In accordance with the norms on pre-trial conciliation, to initiate a small claims procedure classifid as special declaratory, the plaintif must prove compliance with the procedural requirements, that is, provide proof of having exhausted the attempt at conciliation. However, the plaintif may substitute this with the request for and, logically, with the propriety of an interim measure, for which security must be furnished. Conclusions: In small claims procedure, the plaintif must provide proof of having exhausted procedural requirements. Finding an innominate measure in the context of small claims procedure with a view to guaranteeing the effctiveness of the right to credence will be a diffilt task.